Challenges facing emerging contractors in Kwazulu-Natal - Shwala, Lindiwe (My University, 2018)
Challenges facing emerging contractors in Kwazulu-Natal. Despite institutions and programmes in place to develop small, medium, and micro enterprises (SMMEs) contracting firms working in South Africa, the challenges SMME contractors face have persisted; thus, a recurrent concern for construction clients in South Africa. This threatens the sustainability of the industry and that of the economy at large, considering the roles that SMMEs and the construction industry play in the economic development of any country. This study attributed the challenges that the SMME contractors in South Africa’s construction industry to the unique nature of small businesses in South Africa as they go through transformation. The problem stemmed from lack of information on the level of agreement among small contracting businesses in South Africa on the nature of the challenges that they face. This prevents the design and implementation of intervention programmes for capacity building to transform the industry. The study aimed to highlight the challenges faced by emerging contractors in a bid to proffer solutions to address these challenges. Its five objectives were to determine the causes underlying: (1) training needs of the emerging contractors, (2) required business and financial management skills, (3) lack of collateral to access finance, (4) late payments by clients, and (5) limited access to employment opportunities. This study adopted survey research using structured questionnaire to collect data from SMME contractors based in KwaZulu Natal province of South Africa. Participants of CIDB contractor grades 2 to 5 were targeted. 100 questionnaires were administered with a response rate of 65 per cent. On average, the respondents were 36 years old and had 8 years of construction industry working experience. The interval scale data obtained were analysed using descriptive statistics This study observed that South African emerging contractors are characterised by low level of experience and formal construction related training, lack of required skills, lack of access to finance, lack of employment opportunities and lack of cash flows to sustain their businesses due to delays in payment. Therefore, this contributes to failure of emerging contractors to sustain their businesses in the long run. Implications and conclusions are then drawn.
A research report submitted in partial fulfilment to the degree Masters of Science in Building (Project Management in Construction) in the Faculty of Engineering, School of Construction Economics and Management February 2018
Keywords: Constractors--South Africa; Construction constrators--South Africa